Study on the Relationship Between Orthostatic Hypotension and Heart Rate Variability, Pulse Wave Velocity Index, and Frailty Index in the Elderly: A Retrospective Observational Study - Li, Lun; Li, Huanhuan; He, Li; Chen, Hongyan; Li, Yunqiao (Frontiers in Cardiovascular Medicine, 2020)
Background:Orthostatic hypotension(OH) is a common disease of the elderly. It is generally believed that the pathogenesis of OH is related to the impairment of autonomic nerve function and the decreased vascular capacity regulation.This study aims to explore the relationship between OH and heart rate variability (HRV) parameters which reflects autonomic nerve function, ankle-brachial pressure index (ABI) which reflects the degree of vascular stenosis,pulse wave velocity index (PWV) which reflects vascular stiffness, and frailty index (FI) which reflects the overall health status of the elderly. Methods:From January to September 2018, 108 elderly patients with OH and 64 elderly patients underwent physical examination from our hospital were performed 24-hours HOLTER monitoring, PWV and ABI. Analysis software were used to record the subject's the standard deviation of the cardiac cycle(SDNN), the standard deviation of the 5-minute average cardiac cycle(SDANN) ,the square root of the average square sum of consecutive n-interval differences(rMSSD) and the percentage of the number of adjacent cardiac interval differences greater than 50 milliseconds(pNN50),low frequency(LF),high frequency(HF),Very low frequency (VLF),low-frequency / high frequency ratio(LF/HF),. Then FI were evaluated qualitatively and quantitatively in form of scale. Results:There was no statistical difference between the two groups on the basis of age, sex, body mass index(BMI),low density lipoprotein(LDL) resting heart rate, blood pressure, fasting blood glucose, long-term medication, etc.There were significant differences in PWV,SDNN,LF,VLF, LF/HF between the two groups (p<0.05).The risk factor of OH in the qualitative(p=0.04) and quantitative(p=0.007) index FI was higher in OH group than the control group.The risk factors of OH were PWV,SDNN,VLF,LF/HF,FI, where FI was positively correlated and LF/HF was negatively correlated. Conclusions:The pathogenesis of OH is related to vascular stiffness, imbalance of autonomic nerve regulation and its comprehensive health status in elderly.However, arteriosclerosis has not been confirmed as an independent risk factor. Trial registration: Retrospectively registered, http://www.chictr.org.cn.